SWOT Analysis of the Petanque Student Activity Unit Program at Universitas Katolik Santo Agustinus Hippo - Muso Untung; M.E Winarno (CV. SAMODRA INSAN PENA, 2025)
This study aims to evaluate the implementation of the Petanque Student Activity Unit program at the Universitas Katolik Santo Agustinus Hippo using a SWOT analysis approach to identify internal strengths and weaknesses as well as external opportunities and threats that affect program performance. This study used a descriptive quantitative design involving all 16 active members of the Petanque Student Activity Unit, selected through total sampling. Data were collected using a Likert-scale questionnaire covering organizational governance, work programs, human resources, facilities and infrastructure, funding, training implementation, achievements, and evaluation mechanisms. Data analysis was conducted using descriptive statistics and a SWOT analysis to map strategic conditions. The results indicate that the Petanque Student Activity Unit demonstrates dominant internal strengths, particularly in organizational governance, human resource quality, funding and administration, training and coaching implementation, and evaluation mechanisms, all of which are categorized as very good. However, weaknesses were identified in the aspects of work program planning and facilities and infrastructure, which are categorized as good but still need improvement. From an external perspective, significant opportunities are reflected in the organization's high level of achievement and the increasing popularity of petanque in Indonesia, while potential threats include increased competition with other student organizations and limited external funding support. The SWOT matrix reveals that the organization is well-positioned to implement a sustainable development strategy by optimizing internal strengths to capitalize on external opportunities while addressing weaknesses and mitigating threats. In conclusion, the SWOT analysis proved effective in providing a comprehensive strategic evaluation of the Petanque Student Activity Unit program and can serve as the basis for an adaptive, realistic, and sustainable program development strategy within a university sports organization.